Kahook Dual Blade goniotomy in post penetrating keratoplasty steroid-induced ocular hypertension - Rebecca Epstein; Michael Taravella; Mina B. Pantcheva (American Journal of Ophthalmology Case Reports, 2020)
Purpose: Steroid-induced ocular hypertension (OHTN) after penetrating keratoplasty (PKP) may cause irreversible damage to the optic nerve and graft failure. The purpose of this study is to report the first case of a post PKP patient with poorly controlled IOP, successfully treated with Kahook Dual Blade (KDB) goniotomy in both eyes. Observations: The patient was a 62-year old male with prior PKP in both eyes for lattice corneal degeneration. After an uncomplicated phacoemulsification in the left eye, his IOP increased to 32 mmHg on maximum tolerated IOP lowering therapy, including oral acetazolamide. This patient was dependent on scleral contact lenses for his irregular astigmatism post PKP to achieve his best-corrected visual acuity. Thus, we needed to consider a conjunctival sparing procedure and decided to proceed with performing a KDB goniotomy in the left eye. At 29 months follow up the visual acuity (VA) remained at 20/20 and IOP 13 mmHg on dorzolamide/timolol combination drop. A year following, his right eye also required KDB goniotomy combined with cataract surgery to treat his cataract and elevated IOP of 28 mm Hg. At 18 months post KDB goniotomy, the right eye VA was 20/50 and IOP 13 mmHg on dorzolamide/timolol combination drop. Conclusions: This case demonstrates KDB goniotomy may be a good surgical alternative for post PKP steroid-induced OHTN or glaucoma, especially in patients requiring scleral contact lens for their visual rehabilitation.